São José do Norte (RS/Brazil): Environment as a merchandise - dos Santos, Caio Floriano; Puccinelli, Vinicius Ramos; Oliveira, Cleiton Luiz de; Mascarello, Marcela de Avellar; Machado, Carlos RS (Geografares, 2016)
São José do Norte-RS goes through great economic changes which cause a direct impact in the everyday-life of the citizens of the city. These changes are publicised by municipal managers, entrepreneurs and journalists as “progress coming for the city”. The aim of this study is to analyze the acceptance of Grandes Projetos de Desenvolvimento (GPD’s). For this, we have used as data, the articles from the website of the City Hall and reports, among others. As the methodology, we have used the discourse analyze of those materials, which reveal the efforts of the managers to sell the city as an auspicious place for the installation of GPD’s